2022
DOI: 10.1002/adma.202206851
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralized Two‐Enzyme Nanoparticles Regulate Tumor Glycometabolism Inducing Tumor Cell Pyroptosis and Robust Antitumor Immunotherapy

Abstract: Currently, immune checkpoint therapy combined with chemotherapy and radiotherapy is a useful strategy for improving immunotherapy's therapeutic efficacy. However, chemotherapy and radiotherapy cause serious side effects, so finding safe and effective methods to combine with immunotherapy is critical. In this work, regulating tumor glycometabolism is found to induce tumor cell pyroptosis and regulate the degree of expression of programmed death‐ligand 1 (PD‐L1). Therefore, how to treat tumors by regulating tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…The content of IL-1β ( Figure S8 B) and IL-18 ( Figure S8 C) in tumor homogenate also confirmed this result. Previous studies have shown that pyroptosis can induce anti-tumor immune responses 36 , 37 . To investigate the in vivo immune effect, cells from tumor tissues and tumor-draining lymph node (TDLN) tissues were collected to detect the proportion of immune cells using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The content of IL-1β ( Figure S8 B) and IL-18 ( Figure S8 C) in tumor homogenate also confirmed this result. Previous studies have shown that pyroptosis can induce anti-tumor immune responses 36 , 37 . To investigate the in vivo immune effect, cells from tumor tissues and tumor-draining lymph node (TDLN) tissues were collected to detect the proportion of immune cells using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, tumor cells can mediate tumor immune escape by utilizing the PD1 / PDL1 checkpoint [ 76 , 77 ]. Interestingly, recent studies suggested that pyroptosis-induced inflammation could activate anti-tumor immune responses and sensitize cancer cells to anti-PD-1 therapy [ 78 , 79 ]. More importantly, KEGG analysis revealed that PD-L1 expression and PD-1 checkpoint pathway in cancer was enriched in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor volume was measured every 3 days. This was then calculated as follows: V = (length) × (width) 2 /2 (Zhang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%